2011
DOI: 10.1055/s-0031-1278716
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Evaluation of an Injured Vessel Wall Using Fluorescein Sodium before Microvascular Anastomosis in an Experimental Rat Model

Abstract: The aim of this study was to establish an objective evaluation method for intraoperative detection of damaged vascular endothelium in avulsion injuries. Twenty male Fischer rats were randomly assigned to control or experimental groups ( N = 10, each). Crush-avulsion injury was performed on right femoral arteries. Resection of damaged segments was performed according to operative microscopic findings in the control group; fluorescein sodium was applied to the artery lumen before resection in the experimental gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, it also has disadvantages, such as dye entering the surgical field and special equipment being required. Studies aimed at determining levels have been performed, 4,8,[14][15][16] but the standard method is an experimental avulsion model. Level determination was performed histopathologically, and studies have produced no recommendations concerning the practical extent of damage determination capable of use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it also has disadvantages, such as dye entering the surgical field and special equipment being required. Studies aimed at determining levels have been performed, 4,8,[14][15][16] but the standard method is an experimental avulsion model. Level determination was performed histopathologically, and studies have produced no recommendations concerning the practical extent of damage determination capable of use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In practical terms, the extent of injury is determined on the basis of these findings, and previous studies have regarded endothelial findings as more significant. [2][3][4][5][6][7][8][9][10][11][12][13] Experimental methods have been reported concerning the pathophysiology of avulsion injury, 4,8,[14][15][16] but there is no practical method for determining the extent of vascular injury. Although some authors have suggested that endothelial findings are more significant, there is no firm scientific evidence showing which of the clinically used adventitial and lumen findings are more effective.…”
mentioning
confidence: 99%
“…issues if free flap reconstruction is needed [3,4]. In cases of closed fractures, reconstruction of post-traumatic defects is often delayed until skin necrosis has already set in, even if the skin appears intact.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition, the damaged segment of the vessels, the "zone of injury," and the increased thrombogenic effect in this segment may result in late skin necrosis or anastomosis issues if free flap reconstruction is needed. 3,4 In cases of closed fractures, reconstruction of posttraumatic defects is often delayed until skin necrosis has already set in, even if the skin appears intact. It is still uncertain what exactly is happening to the vessels within the injury zone when there is no apparent vascular damage.…”
mentioning
confidence: 99%
“…This could have resulted in lower delayed patency rates, and can be considered as a drawback of the study. Newer modalities like intraoperative near-infrared indocyanine-green (ICG) angiography and mini Doppler systems have been used to evaluate anastomosis patency in the rat femoral vessels (16,20). Though expensive, these techniques could avoid a reexploration surgery to check for delayed patency.…”
Section: █ Acknowledgementsmentioning
confidence: 99%